2016
DOI: 10.1073/pnas.1601935113
|View full text |Cite
|
Sign up to set email alerts
|

Relative influence of meteorological conditions and aerosols on the lifetime of mesoscale convective systems

Abstract: Using collocated measurements from geostationary and polar-orbital satellites over tropical continents, we provide a large-scale statistical assessment of the relative influence of aerosols and meteorological conditions on the lifetime of mesoscale convective systems (MCSs). Our results show that MCSs' lifetime increases by 3-24 h when vertical wind shear (VWS) and convective available potential energy (CAPE) are moderate to high and ambient aerosol optical depth (AOD) increases by 1 SD (1σ). However, this inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 45 publications
(67 reference statements)
0
46
0
Order By: Relevance
“…This permits investigation of the thermodynamic effect of BL humidity (between surface and 950 hPa), free tropospheric relative humidity (between 850 and 400 hPa), low-level VWS, deep tropospheric VWS, and CCN concentrations. Low-level VWS is defined as the difference of the mean wind speed (zonal, since meridional wind difference is smaller) between the two 100 mbar thick layers centering at 937 and 737 hPa (Weisman and Rotunno, 2000); the deep level VWS is the difference between the layers centering at the 887 hPa and 287 hPa pressure levels (Chakraborty et al, 2016;Petersen et al, 2006). We calculate VWS by subtracting the mean wind speed of the top layer from that of the bottom layer.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This permits investigation of the thermodynamic effect of BL humidity (between surface and 950 hPa), free tropospheric relative humidity (between 850 and 400 hPa), low-level VWS, deep tropospheric VWS, and CCN concentrations. Low-level VWS is defined as the difference of the mean wind speed (zonal, since meridional wind difference is smaller) between the two 100 mbar thick layers centering at 937 and 737 hPa (Weisman and Rotunno, 2000); the deep level VWS is the difference between the layers centering at the 887 hPa and 287 hPa pressure levels (Chakraborty et al, 2016;Petersen et al, 2006). We calculate VWS by subtracting the mean wind speed of the top layer from that of the bottom layer.…”
Section: Methodsmentioning
confidence: 99%
“…For example, VWS influences the rainfall and total condensation within developing convection (Weisman and Rotunno, 2004), slantwise ascent of the parcel (Moncrieff, 1978), storm rotation, maintenance, vorticity, updraft speed (Weisman and Rotunno, 2000), and lifetime (Chakraborty et al, 2016). Though detailed microphysical properties are not considered in our simple plume calculations, it is worth noting that a recent study by Wu et al (2017) found that lower tropospheric wind shear promotes the droplet collision and growth inside the shallow clouds by the production of turbulent kinetic energy.…”
Section: Examining Indirect Thermodynamic Effects From Shear and Ccn mentioning
confidence: 99%
See 2 more Smart Citations
“…However, many previous studies 34 illustrate difficulties in representing the shallow-deep evolution in models (Del Genio and Wu,35 2010; Waite and Khouider, 2010 influencing the slantwise ascent of the moisture (Moncrieff, 1978), separating the updraft and 48 downdraft regions. In a recent study, it was shown that deep tropospheric VWS (DVWS) has a 49 significant impact on the lifetime of mesoscale convective systems (Chakraborty et al, 2016) 50 and can regulate the anvil's formation (Koren et al, 2010;Weisman and Rotunno, 51 2004; Petersen et al, 2006;Kilroy et al, 2014;Harrison, 1992) as well as the updraft speed of the 52 parcels (Weisman and Rotunno, 2004). On the other hand, low level VWS (LVWS) can influence 53 the rainfall and total condensation within developing convection (Weisman and Rotunno,54 2004).…”
mentioning
confidence: 99%